Psycho-social factors and management of student discipline in Ibadan rural secondary schools (2017)
The problem of indiscipline among adolescents and youth in the Nigerian secondary school system has been a subject of discontent to stakeholders spanning decades. On management of disciplinary issues, urban schools receive more attention than rural schools. It is also observed that most student’s migrate from rural to urban schools after acquiring vices hence the problem remain unabated. Severed factors have been investigated previously but this study concentrated its investigation on psycho-social factors (peer pressure, parental influence and social factors and disciplinary problems. The study used the individual theory and Bandura's theory of social learning as its theoretical framework. The survey research design was adopted using purposive sampling technique to select Oluyole Local Government Area (LGA). Out of 23 secondary schools in the LGA, 50% i.e. 12 where randomly selected for the study with a student population of 10% that resulted into 300 respondents. A researcher developed instrument titled 'Psychosocial Factors and Disciplinary Issues Questionnaire’ (PFDIQ) ‘r’-0.76 was used for the study after validity test by colleagues in the Faculty of Education of the University of Ibadan and a trial test among similar subjects. The 5 developed hypotheses were tested with Pearson product moment correlation coefficient (PPMC) and multiple regression analysis @p<0.05 level of significance. Result indicated a significant relationship between peer pressure and indiscipline r = 0.015;p<0.05, parental influence and indiscipline r=0.234;p<0.05, social factors and indiscipline r-0.002;p<0.05. There were relative contributions and joint influences but recommendations included strengthening current disciplinary measure and introducing more via joint efforts between the homes and the schools.